Neutron diffraction residual stress determinations in titanium aluminide component fabricated using the twin wire-arc additive manufacturing. (February 2022) - Shen, Chen; Ma, Yan; Reid, Mark; Pan, Zengxi; Hua, Xueming; Cuiuri, Dominic; Paradowska, Anna; Wang, Lin; Li, Huijun
Abstract: In recent years, twin wire-arc additive manufacturing (T-WAAM) technique has been considered as a promising method of fabricating and shaping titanium aluminide components with high efficiency and low cost. However, excessive thermal input of the non-consumable tungsten electrode arc deposition induces significant residual stresses in the buildup component, thus accurate measurement of residual stresses is necessary for T-WAAM buildup part quality assessment. In the present research, non-destructive neutron diffraction residual stresses measurements on as-fabricated and heat-treated T-WAAM produced Ti48Al titanium aluminide components are performed. To exclude the influence of initial large T-WAAM residual stresses on d 0 hkl sample alignment, different d 0 hkl sample dimensions are designed: one is normal thin slice and the other is the meshed sample. According to the obtained results, the conducted post-production heat treatment has partially released initial residual stresses. Also, the meshed design of d 0 hkl sample shows better measurement accuracy than the simple sliced d 0 hkl sample. In addition, T-WAAM fabricated titanium aluminide wall component performs featured tensile-compressive alternating residual stress distribution induced by the layer-by-layer arc deposition.